Trade Policy and Economic Growth: A Selective Survey - بوخشيم, عبدالناصر (Dirasat in Economics and Business, 2008)
Trade Policy and Economic Growth: A Selective Survey Dr. Abdul Nasser E. Boukhsheim Economics dept, Faculty of Economics, University of Garyounis Since Adam Smith, interest in trade policy has been driven with the debate about the trade policy appropriate to enhance economic growth. This relationship is still one of the most controversial issues in the modern economic literature. According to the pioneer works of Singer and Prebisch (1950), terms of trade tend to deteriorate systematically against the primary commodities exported by the less developed countries (LDCs) in the long run. This hypothesis had strongly affected the suggestions related to the debate about trade policy and economic growth during the 1950s and the 1960s in particular. The unsatisfactory results accompanied with the applying of the import substitution strategy and protectionism in the vast majority of the LDCs leaded to a wide consensus in the 1980s and 1990s to turn inversely to trade liberalization by emphasizing on the importance of the out-ward orientation strategies to achieve development goals. This paper implies a selective survey about the most important contributions in both theoretical and empirical sides related to this old - contemporary issue.